Region level risk factors for the Ebola virus disease in West Africa - Levy, Benjamin; Odoi, Agricola (PeerJ Preprints, 2017)
Background. The Ebola Virus Disease (EVD) is a highly infectious disease that has claimed over 25,000 cases in the past 50 years. While many past outbreaks of EVD resulted in relatively few incidents, the 2014 outbreak in West Africa was the most deadly occurrence of EVD to date producing over 15,000 confirmed cases. Objective. In this study we relate total confirmed case counts of EVD to predictor variables at the region level in Sierra Leone, Liberia, and Guinea. Methods. We used a Poisson framework and negative binomial framework to relate the predictors to the outcome. A spatial analysis was conducted to further our understanding and help interpret results. Results. Results indicate that the percent of the population living in urban areas, percent of household with a bad quality or no toilet, and percent of married men working in blue collar jobs protect against the transmission of EVD. Our study also shows that mean years of education contributes to increased case counts of the disease. Conclusions. Each significant predictor are associated with the types of dynamics that either protect against, or exacerbate, the spread of EVD. While having limited contact with the bodily fluids of others, reduced person-to-person contact, and isolated population clusters protect against the spread of EVD, the types of daily interactions an educated individual will experience leads to higher incidence rates. This information can be used to identify potential transmission routes and prevent future outbreak of this deadly disease.
Keywords: Ebola; West Africa; Negative Binomial Regression; Poisson Regression; Statistical Modeling